HOW DOES ONLINE TAX DECLARATION OF BUSINESSES - INFLUENCE THE WAY THE TAX OFFICES ARE ADMINISTERED IN SHKODRA - Bashi, Elidiana; Dibra, Mirjam (European Scientific Journal, ESJ, 2014)
Public services and their management have a great influence in the development of the local economy of a country. During the process of transformation of the community in an intense computing system of information, the offering of these services through information technology, in an effective, fast, transparent and safe mannerin accordance with citizens and businessneeds are very important. Referring to makers of online declaration, this is an important measurethat will influence in increasing the effectiveness of tax administration, to minimize the tax evasion in labour market, and to facilitate the exchange between two important institutions: Tax Office and Social Insurance directory. However, this online information exchange between these two institutions, aims in facilitating the data exchange between these two directories, with the purpose of establishing a clear evidence of the data of social insurance payments from that of businesses and citizens. This exchange will help the history creation, for each social insurance payer, thereby helping them in having the necessary profits from these paid contributions.